Efficient privacy protection scheme with batch verification in smart grid - Wang, Mingxiang; Zhang, Lei (Frontiers in Energy Research, 2024)
Smart grids can establish two-way communication with users, collect their electricity consumption data and provide reasonable pricing, but fine-grained electricity consumption data leads to the leakage of user privacy. In order to protect the privacy of user data and the security of data transmission process, this article proposes an efficient and batch validated privacy protection scheme. In this scheme, legitimate entities transmit encrypted electricity data after mutual authentication. To ensure the correct data is received, we propose a new batch signature verification algorithm. Security analysis shows that our solution achieves user privacy and data security. The simulation experiments provided demonstrate that the efficiency of the proposed scheme can satisfy the requirements of real-time communication.